Development and validation of QRISK3 risk prediction algorithms to estimate future risk of cardiovascular disease: prospective cohort study - Hippisley-Cox, Julia; Coupland, Carol; Brindle, Peter (BMJ Publishing Group, 2017)
Objectives: To develop and validate updated QRISK3 prediction algorithms to estimate the 10 year risk of cardiovascular disease in women and men accounting for potential new risk factors.